Environmental concern, attitude and intention in understanding student’s anti-littering behavior using structural equation modelling - Ibrahim, Hayati; Mariapan, Manohar; Lim, Evelyn Ai Lin; Bidin, Sheena (Multidisciplinary Digital Publishing Institute, 2021)
Concerns about the environment began to rise as various issues such as littering increased. Littering is one of the problems involving the environment, and higher education campuses are also actively practising anti-littering to show their efforts. The aim of this study is to test the relationship between environmental concern, attitude and intention on anti-littering using Theory of Planned Behavior Extended Model. A total of 303 students of the Polytechnic Malaysia campus were respondents in this study and the data were analyzed by Structural Equation Modeling using SPSS Amos 24.0 Statistical Packages. Findings show that there is a direct and indirect effect between environmental concern and student’s anti-littering intention. The indirect result shows that attitude towards anti-littering behavior partially mediates the relationship between environmental concern and anti-littering intention. The implications of the research findings and suggestions for the future study are also included in the study.